Health Monitoring System for Induction Motors (International Journal of Engineering and Computer Science, 2017)
To avoid unexpected equipment failures and obtain higher accuracy in diagnostic c for the predictive maintenance of induction motors, on-line health nitoring system plays an important role to improve the system reliability and availability. Among different techniques of fault erection, work on motor current signature analysis by using only stator current spectra has been well documented. In addition, the recent developments in MEMS technology shows increasing trend in integrating vibration analysis for fault diagnostic. Vibration-based detection by using the accelerometer is gaining popularity due to high reliability low power consumption, and low cost. A electric machine based on wireless sensor network (ZigBeeTM/IEEE802.15.4